Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1182/blood-2016-07-724419
|View full text |Cite
|
Sign up to set email alerts
|

DREAM plays an important role in platelet activation and thrombogenesis

Abstract: Downstream regulatory element antagonist modulator (DREAM), a transcriptional repressor, is known to modulate pain responses. However, it is unknown whether DREAM is expressed in anucleate platelets and plays a role in thrombogenesis. By using intravital microscopy with DREAM-null mice and their bone marrow chimeras, we demonstrated that both hematopoietic and nonhematopoietic cell DREAMs are required for platelet thrombus formation following laser-induced arteriolar injury. In a FeCl-induced thrombosis model,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 50 publications
3
18
0
Order By: Relevance
“…Indeed, we have recently shown that the mRNA and protein of DREAM is expressed in human and mouse platelets and a human megakaryocyte cell line (12). DREAM deletion did not affect blood counts in mice, and DREAM bone marrow chimeric mice showed no difference in their blood counts, suggesting that DREAM is dispensable for hematopoiesis.…”
Section: Role Of Dream In Platelet Functionmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, we have recently shown that the mRNA and protein of DREAM is expressed in human and mouse platelets and a human megakaryocyte cell line (12). DREAM deletion did not affect blood counts in mice, and DREAM bone marrow chimeric mice showed no difference in their blood counts, suggesting that DREAM is dispensable for hematopoiesis.…”
Section: Role Of Dream In Platelet Functionmentioning
confidence: 99%
“…In a series of functional assays, we found that DREAM deletion significantly reduces granule secretion, cytosolic Ca 2+ levels, αIIbβ3 integrin activation, and aggregation in platelets following stimulation with a low concentration of agonists such as thrombin, CRP, U46619, A23187, and ADP (12). Interestingly, our study using isoform-specific PI3K inhibitors (42, 43) in DREAM-null platelets provided evidence that the regulation of platelet function by DREAM results from activation of PI3K class Iβ after agonist stimulation.…”
Section: Role Of Dream In Platelet Functionmentioning
confidence: 99%
See 3 more Smart Citations